Implementasi Kebijakan Dewan Perwakilan Daerah Republik Indonesia Dalam Pengawasan Bidang Pendidikan - Rezky Adithya; Diana Prihadini (Reformasi Administrasi, 2026)
The 1998 reform brought major changes to the constitutional system, including Regional Autonomy and amendments to the 1945 Constitution, which established the DPD RI as part of a bicameral system with the DPR RI. This research examines the implementation of DPD RI supervision of education policies, especially Law no. 20 of 2003. Using descriptive qualitative methods, it was found that the authority of the DPD RI is limited, only giving consideration to the DPR RI because the government oversight function lies with the DPR. Optimizing the role of the DPD RI can be done through better political consolidation. The Constitutional Court's decisions (No. 92/PUU-X/2012 and No. 79/PUU-XII/2014) emphasize the role of the DPD RI, but the effectiveness of the bicameral system requires changes to the 1945 Constitution and regulations to strengthen the authority, duties and functions of the DPD RI.